12‐1: Invited Paper: Stretchable Transparent Electrodes Based on Silver Nanowires. Issue 1 (May 2017) - Tong, Kwing; Chen, Dustin; Liang, Jiajie; Pei, Qibing
Abstract : Silver nanowire (AgNW) ‐polymer composite electrodes have been developed as a viable replacement for ITO/glass and ITO/PET, with added benefits of high mechanical flexibility. The sheet resistance can be adjusted in the range from 5‐50 Ω/sq with transmission ranging from 70 to 90%. The surface roughness is generally <2 nm, suitable for the fabrication of thin film electronic devices. The mechanical properties of the composite electrodes are almost entirely determined by the polymer substrate used and can be made flexible, stretchable, shape memorable, or even self‐healable. Malfunctions of resulting touch sensors due to crack formation could be mended by heating. Polymer OLEDs fabricated using a pair of stretchable AgNW/polyurethane electrodes could be stretched by >100% strains and repeatedly stretched by 30% strains. Integrated substrates designed specifically for OLED lighting could improve the light extraction efficiency of the OLEDs by up to 2.5X.